EVALUATING THE SYTEM OF POWER SHARING ETHIOPIA IN LIGHT OF AREND LIJPHART’S MODEL OF POWER SHARING - Belay, Alefe Abeje (European Scientific Journal, ESJ, 2013)
Ethiopia has deep linguistic and religious diversities. Because of lack of accommodation of these diversities the country was plagued by internal conflicts and civil wars. True, power sharing is very essential to any accommodation of deep diversities. The goal of this paper is evaluate the system of power-sharing in Ethiopia in light of the Arend Lijphart’s theory of power sharing. It identifies power-sharing as the most fundamental conflict management strategy adopted to deal with diversities. The article argues that the Ethiopia’s power-sharing model, which is largely consociational, is less suitable to Ethiopia as compared to more centripetal model of power-sharing.